PERAN KELUARGA DALAM MENDIDIK ANAK USIA DINI SELAMA PANDEMI COVID-19 - Mahartini, Komang Trisna (Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
This study aims to describe early childhood education in families in a COVID-19 pandemic situation; the obstacles faced in educating early childhood in families in the COVID-19 pandemic situation; and efforts made to overcome the obstacles to educating early childhood in families in the COVID-19 pandemic situation. This type of research is descriptive qualitative. The location of this research research is in Padangbulia Village, Sukasada District, Buleleng Regency. The research subjects were parents of early childhood as informants, totaling 20 people. The data used are primary and secondary data. The technique of determining informants is purposive sampling. Data collection techniques by means of literature study and interviews. The data were then analyzed through the stages of data collection, reduction, display, and verification. This research reveals several things including: early childhood education in the family in the COVID-19 pandemic situation, including the feelings of parents when replacing the role of teachers, the readiness of parents to educate children during the COVID-19 pandemic; and the role of parents in helping children learn. The obstacles faced when educating early childhood in the family in the COVID-19 pandemic situation are children's boredom, differences in children's learning styles, learning atmosphere, learning facilities and learning comfort. Efforts made in overcoming obstacles when educating early childhood in the family in the COVID-19 pandemic situation are that parents must learn more, pay attention to children's learning habits, prepare adequate supporting facilities, and create a comfortable learning atmosphere.